THE ANALYSIS OF CODE MIXING IN SENIOR HIGH SCHOOL WR. SUPRATMAN 2 MEDAN - Clara Novita; Kristina Elisabet; Hutahean, Maria; Zalukhu, Wetby Alvania Valentini; Tarigan, Sri Ninta (ELT (English Language Teaching Prima Journal), 2021)
AbstractThe purpose of this research is to analyze which types of code-mixing are often used by students atW.R. Supratman 2 School. In this research, the researchers used methods of recording andanalyzing conversations between students in the school environment, this research used qualitativeresearch methods. This research shows which types of code-mixing are often used by students andwhy students use code-mixing. The results of the data obtained by the researchers state that intrasentential code-mixing is a type often used by students. The reason why students often use code-mixing in daily conversations is that they always use someone's quote in English to motivatelearning English, to express emotions or feelings among friends, they want to look cooler and moreattractive and the last reason is that sometimes they find words that have no representation inother people.Keyword: Code Mixing, Sociolinguistic